Development of Virtual Laboratory-based Learning Media on Sensor and Actuator Device Elements - Nisa, Khoirotun; Handayani, Anik Nur (Lectura : Jurnal Pendidikan, 2025)
Today’s technological advancements can be used to suit the demands of many areas of life, including education. Technology in education enables more flexible medium for learning. Limited laboratory facilities in vocational high schools hamper practicum activities that are very important to achieve the standard competence. Virtual laboratory-based learning media is needed to simulate theory and practicum activities without time and place restrictions. This research aims to develop and calculate the feasibility of virtual laboratory-based learning media in the form of guidebooks and job sheets for sensor and actuator subjects using the Wokwi platform, arduino simulation projects, and sensors. This research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with data collection through observation, interviews, validation by media experts and material experts, and trials to students. Data were analyzed qualitatively and quantitatively. This study involving 77 students from class XI of Industrial Automation Engineering (Teknik Otomasi Industri/TOI) SMK PGRI Singosari showed results that the teaching materials achieved a combined validity value of 92.41% for the guidebook, 93.88% for the job sheet, and 93.20% for the Wokwi platform. The combined validity value ranges from 85.01% to 100% which indicates that the teaching materials are very valid and suitable for use. In conclusion, this virtual laboratory-based learning media supports the understanding of sensor and actuator subjects in vocational education. This learning media effectively overcomes the limitations of laboratory facilities while increasing student learning motivation.